Humidity assisted annealing technique for transparent conductive silver nanowire networks1. Issue 25 (21st March 2015) - Weiß, Nelli; Müller-Meskamp, Lars; Selzer, Franz; Bormann, Ludwig; Eychmüller, Alexander; Leo, Karl; Gaponik, Nikolai
<x xml:space="preserve">Abstract</x> The capacity of polyvinylpyrrolidone (PVP) to adsorb water vapor was used to decrease the sheet resistance of silver nanowires (AgNW) based electrodes.